Modern weapons and military equipment for the issue 1-2025 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2025)
New high-energy lightweight laser systems; Next-generation hydrogen-powered K3 tank; New Chinese HQ-19 surface-to-air missile system